Geometry equation
 👍 0
 👎 0
 👁 119
Respond to this Question
Similar Questions

Math (Calculus II) (Weird Work Problem Setup Help)
I am trying to understand my teacher's example of a Work problem. Cut to the chase here's a picture of the problem: goo.gl/photos/AqZ6ENmHLg6heixD7 While I understand how to integrate fairly well, I'm still confused on how exactly
asked by Ray on May 15, 2017 
algebra
in solving the equation (x +2)(x  2) = 32 eric stated the solution to be x + 2 = 32 => x = 30 or x 2 = 32 => x = 34. however at least one of these solutions fails to work when plugged back into the equation. why is that? please
asked by Theresse on September 29, 2012 
Geometry
Need help please: (3,0) (7,6) (x7)2 + (y6)2 = 7(2) (x7)2 + (y6)2 = 49 Having difficulty with this problem.Can someone help? geometry  Reiny, Saturday, March 31, 2012 at 8:07am You don't say what the actual problem is. I see
asked by Kel on March 31, 2012 
Geometry
Need help please: (3,0) (7,6) (x7)2 + (y6)2 = 7(2) (x7)2 + (y6)2 = 49 Having difficulty with this problem.Can someone help? geometry  Reiny, Saturday, March 31, 2012 at 8:07am You don't say what the actual problem is. I see
asked by Kel on March 31, 2012 
Math
I don't understand how to solve this problem: In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work
asked by Angelina on August 22, 2011 
Cosmology
The equation describing the geometry and massenergy distribution of a homogeneous and isotropic universe is known as:  The Einstein Equation  The Friedmann Equation  The RobertsonWalker Equation  The Hubble Equation
asked by qwerty on January 8, 2013 
math
In solving the equation (x + 4)(x – 7) = 18, Eric stated that the solution would be x + 4 = 18 => x = 22 or (x – 7) = 18 => x = 11 However, at least one of these solutions fails to work when substituted back into the
asked by carol on May 4, 2011 
Algebra
In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original
asked by Sierra on October 13, 2011 
algebra
1. In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original
asked by Taina on June 20, 2011 
algbera
In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original
asked by kozy on May 1, 2011